Experimental Comparison of Interference and Autocollimating Null Indicators - B. Nyamweru; E. V. Shishalova (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. At present, measurement of angles with high accuracy is an essential task in various scientific and industrial fields. The goniometer is one of the most widespread high-precision angle measuring devices, which can incorporate various types of null indicators. In turn, null indicators (NI) are based on different operating principles and can be sensitive to external factors that contribute to the measurement error.Aim. Experimental comparison of two NI types: an interference NI with a Koester prism and an autocollimating NI based on a quadrant photodiode.Materials and methods. An experimental setup was assembled, including two NI that could be connected to one goniometer and measure the accumulated angles of one optical polygon under the same conditions.Results. As a result of conducting measurements and performing a cross-calibration procedure, four sets of data were obtained. An analysis of the processed data showed that the difference in the errors of the ring laser when using two NI did not exceed 0.06 arc seconds, being within the margin of random error. At the same time, the difference between the deviations of the reflecting faces from the nominal position for the two faces exceeded this limit, which confirms the effect of deviation of the surface from the plane on angular measurements with different types of null indicators.Conclusion. According to the results obtained, from the random error point of view, the interference null indicator NI showed higher performance, demonstrating the RMS of measured values of 0.02 angular seconds when measured during 25 prism revolutions. At the same time, the autocollimating null indicator NI had an RMS at the level of 0.04 angular seconds when measured during 64 revolutions. Presumably, this may be caused by the installation specifics of NI. It should also be noted that there is no correlation between the statistical characteristics of the reflecting face itself and the difference between its deviations determined by different NI types.